BENTUK KONSEP HEGEMONIE DALAM FILM â€œDIE WELLEâ€ KARYA DENNIS GANSEL - NURTAVIOLA WIDYASWARI, MARSYELA (IDENTITAET, 2016)
Hegemony is a leadership von Antonio Gramsci (in Faruk, 2010: 132). A social groups must be able to carry out the leadership before winning governmental power. To be dominant  authority when obtain, even if it already holds such dominant it must continue to leadership. Leadership is what is called hegemony. Based on the above theory, the problem in this research is: how to shape of hegemony in the film “Die Welle” by Dennis Gansel? The purpose of this study is to describe the form of hegemony in the film “Die Welle” by Dennis Gansel. This research include in descriptive qualitative research. Furthermore, to analyze used theory of hegemony von Antonio Gramsci, have the form concept of hegemony: (1) the form concept of cultural, (2) the form concept of hegemony, (3) the form concept of ideology, (4) the form concept of belief popular, (5) the form of the intellectuals, and (6) the form concept form of the state. The analysis technique used is as follows: (1) Data that has been determined is then analyzed based on the theory that has been specified in chapter 2, namely the theory of hegemony, (2) Data that has been analyzed and then described, in order to achieve the objectives that describe the form of hegemony in the film “Die Welle”, (3) Select the data that is considered the most prominent will then be included in the discussion section, (4) the final step is to draw conclusions. The analysis show that the quotation of dialogue in the film “Die Welle” by Dennis Gansel have 1 the form concept of cultural, 5 forms concept of hegemony, 10 forms concept of ideology, 1 the form concept of popular belief, 2 forms concept of the intellectuals, and the 3 forms concept of the state. Keywords: Hegemony, Movie, Gansel